Pandangan Teologis Tentang Hubungan Suami Istri Menurut Efesus 5:22-25 - Silviana Silviana; Teguh Parluhutan; Rode Sri Rahayu (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Marriage in the Christian context is considered sacred because it is established by God as a depiction of the union between Christ and His church. However, the current reality shows a lack of holiness in Christian marital relationships. This writing addresses this issue by referencing biblical texts and the realities of Christian life. This paragraph explores theological views on the husband – wife relationship, emphasizing the importance of Christ's love and humility in marriage, as taught in Ephesians 5:22-25. Additionally, it highlights the importance of premarital counseling in preparing couples for the challenges of marriage. Psalm 90:10 is also used as a guide for facing difficulties and suffering in life. By considering biblical guidance and life realities, this writing emphasizes the importance of involving God in every aspect of marital life. The research method used is a theological approach, examining various biblical texts connected to Ephesians 5:22-25 and theologians' interpretations.